2021
DOI: 10.4067/s0718-381x2021000200443
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Protocol For Topical Application of Capsaicine Gel 0.025 % in the Management of Burning Mouth Syndrome Correlating its Impact on Quality of Life

Abstract: of a protocol for topical application of capsaicine gel 0.025 % in the management of burning mouth syndrome correlating its impact on quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 12 publications
0
0
0
Order By: Relevance
“…Topical capsaicin was applied for a period of 28 days (excluding the washout period of 14 days) in the study by Jørgensen and Pedersen 23 . The capsaicin application duration was the longest at 180 days in the study by Ricken et al 24 . Three weeks continuous capsaicin topical application as mouthwash three times a day was used in the study by Jankovskis and Selga 22 .…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…Topical capsaicin was applied for a period of 28 days (excluding the washout period of 14 days) in the study by Jørgensen and Pedersen 23 . The capsaicin application duration was the longest at 180 days in the study by Ricken et al 24 . Three weeks continuous capsaicin topical application as mouthwash three times a day was used in the study by Jankovskis and Selga 22 .…”
Section: Discussionmentioning
confidence: 90%
“…Remission of the symptoms of BMS was observed as early as 28 days in the study by Jørgensen and Pedersen 23 . The study by Ricken et al 24 reported remission of symptoms in 50% of the patients and significant improvement in 40% in the first 30 days. Ricken et al 24 also performed evaluation after 180 days and after medication withdrawal, and 60% of the patients reported total absence of BMS symptoms.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations